(3JGQjN fLOs - (3ebHd Hf YHO GdYRjR GdPcjQ , fMh (B1360 (3g`s
(3ChdgG (B:s
(3fLQGf (B: (3HdGO hGSYI s
(3BNQgG (B:s
(3hai SfI (B1282 (3Jhaj GdEeGe ajUd JQLeI MjGJg s
(3ef GdfSNI faSgGs
(3hHChdgG agQSJs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B281s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B89 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs